SSM‑RA: A Novel Sharp‑Notch Metamaterial SRR Antenna with EBG Ground for Plasma‑Resilient Reentry Communication - Rengaraj, Saravanakumar; Shieh, Chin‑Shiuh (Digital Technologies Research and Applications, 2025)
Reliable communication during atmospheric reentry is strongly affected by plasma induced attenuation. Antennas for such missions must remain compact, thermally robust, and maintain stable impedance while supporting directive radiation in the C‑band. Conventional microstrip and Fabry‑Perot cavity antennas often experience radiation distortion and reflection loss under reentry conditions, and their use of extra reflectors or cavities restricts integration within thermal protection systems. This work presents the Sharp‑Notch Split‑Ring Metamaterial Reentry Antenna (SSM‑RA), an angle oriented Split‑Ring Resonator antenna with an EBG backed defected ground optimized for dual‑band C‑band operation. Sharp‑notch SRR slots placed at specific angles improve directional gain, suppress surface waves, and support polarization stability under elevated temperatures. Full wave simulations in Ansys HFSS over 3−6 GHz are used to study gain, directivity, return loss, and VSWR. The antenna is realized on an Arlon 10FR substrate and characterized using a vector network analyzer. Measurements yield gains of 3.01 dB and 4.63 dB at 3.7 GHz and 5.05 GHz, with return loss of −13.38 dB and −28.85 dB and radiation efficiencies of 67.06% and 87.33%. Relative to a conventional C‑band microstrip reference on the same substrate, SSM‑RA provides higher gain, deeper impedance minima, and broader bandwidth, with percentage improvements quantified in the comparison section.